Searching for improved mimetic peptides inhibitors preventing conformational transition of amyloid-β42 monomer - Gera János (BIOORGANIC CHEMISTRY, 2018)
A series of novel mimetic peptides were designed, synthesised and biologically evaluated as inhibitors of Aβ42 aggregation. One of the synthesised peptidic compounds, termed compound 7 modulated Aβ42 aggregation as demonstrated by thioflavin T fluorescence, acting also as an inhibitor of the cytotoxicity exerted by Aβ42 aggregates. The early stage interaction between compound 7 and the Aβ42 monomer was investigated by replica exchange molecular dynamics (REMD) simulations and docking studies. Our theoretical results revealed that compound 7 can elongate the helical conformation state of an early stage Aβ42 monomer and it helps preventing the formation of β-sheet structures by interacting with key residues in the central hydrophobic cluster (CHC). This strategy where early “on-pathway” events are monitored by small molecules will help the development of new therapeutic strategies for Alzheimer’s disease.